METODE JIGSAW DI MTS.S NU SIBORONG-BORONG DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Mardliya Harahap (CV. ADIBA AISHA AMIRA, 2024)
Students consider the History of Islamic Culture lesson to be a boring and tedious lesson. This problem occurs because the teacher is not creative enough in learning activities (using the same methods). Therefore, to try to make students learn more actively, think more critically, participate more in the learning process or learning and learning, more interested in learning. Educators (teachers) must be able to condition students, and use the right method, so that students are more interested in the process of learning the History of Islamic Culture. Based on the background of the problem above, the researcher is interested in raising this problem into a study in the form of a written work entitled